2009 International Conference on Field Programmable Logic and Applications 2009
DOI: 10.1109/fpl.2009.5272272
|View full text |Cite
|
Sign up to set email alerts
|

Efficient particle-pair filtering for acceleration of molecular dynamics simulation

Abstract: The acceleration of molecular dynamics (MD) simulations using high performance reconfigurable computing (HPRC) has been much studied. Given the intense competition from multicore and GPUs, there has been a question whether MD on HPRC can be competitive. We concentrate here on the MD kernel computation: determining the short-range force between particle pairs. In particular, we present the first FPGA study on the filtering of particle pairs with nearly zero mutual force, a standard optimization in MD codes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…In previous work [12], [13], we reported an expected running time of 22ms per iteration for the accelerator execution of the short-range force. This number is based on the following assumptions:…”
Section: A Initial Performance Profilementioning
confidence: 97%
See 1 more Smart Citation
“…In previous work [12], [13], we reported an expected running time of 22ms per iteration for the accelerator execution of the short-range force. This number is based on the following assumptions:…”
Section: A Initial Performance Profilementioning
confidence: 97%
“…Although there have been many FPGA implementations (e.g., [5], [6], [7], [8], [9], [10], [11]), the heavy use of floating point in MD appeared to make these less competitive. In recent work [12], [13], however, we have shown that when FPGAs perform particle filtering (on-the-fly neighbor list generation), much of the floating point computation can be eliminated. As a result, FPGA-based MD acceleration is not only viable, but when power considerations are factored in, potentially an excellent fit.…”
Section: Introductionmentioning
confidence: 99%
“…2. MD software system = ProtoMol, FPGA = Altera Stratix III [11], [2]. The significance of the Stratix III is that it has improved floating point support.…”
Section: Polynomial Evaluationmentioning
confidence: 99%
“…In (Gu et al, 2008), the force pipeline was extensively explored. (Chiu et al, 2008;Chiu and Herbordt, 2009) (Herbordt, 2013) researched the approaches of the architecture/algorithm codesign of MD processors. (Herbordt et al, 2007;Herbordt et al, 2008;Khan et al, 2013;Vancourt and Herbordt, 2009) provide general overviews of these methods.…”
Section: Previous Work Of 3d Ffts On Fpgasmentioning
confidence: 99%